2022
DOI: 10.1038/s41598-022-10733-8
|View full text |Cite
|
Sign up to set email alerts
|

Inequality and cooperation in social networks

Abstract: Social networks are fundamental to the broad scale cooperation observed in human populations. But by structuring the flow of benefits from cooperation, networks also create and sustain macro-level inequalities. Here we ask how two aspects of inequality shape the evolution of cooperation in dynamic social networks. Results from a crowdsourced experiment (N = 1080) show that inequality alters the distribution of cooperation within networks such that participants engage in more costly cooperation with their wealt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 25 publications
0
14
1
Order By: Relevance
“…Aiello 79 used a model of ten social relation dimensions from social psychology to evaluate social tie strength and found that high-quality social connections can effectively enhance an individual's economic opportunities and performance.Chetty 80 argued that there exists a notable correlation between the rise of social capital and the robustness of social interaction networks. Melamed 81 showed that the cooperative structure of social networks and the asymmetry of social capital reinforce each other, ultimately resulting in systemic inequality within society. Within this article, the terms 'strong connection' and 'weak connection' are used to describe the varying levels of intensity present within interpersonal interaction networks.…”
Section: Discussionmentioning
confidence: 99%
“…Aiello 79 used a model of ten social relation dimensions from social psychology to evaluate social tie strength and found that high-quality social connections can effectively enhance an individual's economic opportunities and performance.Chetty 80 argued that there exists a notable correlation between the rise of social capital and the robustness of social interaction networks. Melamed 81 showed that the cooperative structure of social networks and the asymmetry of social capital reinforce each other, ultimately resulting in systemic inequality within society. Within this article, the terms 'strong connection' and 'weak connection' are used to describe the varying levels of intensity present within interpersonal interaction networks.…”
Section: Discussionmentioning
confidence: 99%
“…Altruism, understood as those actions developed with a deliberate focus on benefiting others, rather than oneself (such as the decision to participate in activities like recycling, blood donation, or programs to support the poor), can play an essential role in shaping the future of modern societies, and studying it could provide insight into the mechanisms that drive it. Ultimately, understanding said mechanisms could serve to inform public and regulatory entities about widespread collaborative behavioral traits, thus equipping them to develop more comprehensive, holistic and effective regulatory frameworks to address some of the most relevant sociological problems, such as the climate emergency 1 , 2 , the emergence of social inequality 3 or increasing socioeconomic polarization 4 , 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Inequality has shaped the evolution of cooperation since the times of the hunter-gatherer society (Apicella et al, 2014). Inequality in wealth affects social preference (Melamed et al, 2022), facilitates social segregation (Nishi et al, 2015), and decreases subjective well-being and happiness in the segregated population (Buttrick et al, 2017). Given the detrimental consequences of inequality, encouraging resource sharing between the rich and the poor becomes an important issue in human society (Haynie et al, 2021).…”
Section: Introductionmentioning
confidence: 99%